Hazel Neithercut: capstone - Neithercut, Hazel, artist (Colorado State University. Libraries, 2016)
The artist's statement: Through my work, I hope to show effective, interesting and fresh designs. Taking influence from many different types of media, my work is meant to create a story, with every aspect of color, illustration and type playing an essential role in telling it.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design